PENGISIAN PARTOGRAF DI BIDAN PRAKTIK SWASTA - Kartini, Farida (Jurnal Media Ilmu Kesehatan, 2013)
Background: Partograf is used to monitor the progress of labor. By using patograf can assess the state of mother and the baby, so when there is an abnormal condition, then midwife could take the right  actions and clinical decisions immediately. Objectives: To investigate the utilization of partograf by midwives private practice. Methods: The research was a qualitative research with phenomenology approach. These were five informant who got involve in this study. All of them are midwives who conduct their own private practice in Yogyakarta. Sampling technique used in this study was purposive sampling. Data collection used was through indepth interview. Results: Perception of midwives on partograf, time needed to fill partograf and reason of midwives for not always using partograf are the 3 themes found in this study. This study also identified the completeness and the accuracy of partograf filling. Conclusion: In Yogyakarta, not all midwives using partograf in an orderly manner. There should be a maintainance program regarding the utilization of partograf for midwives private practice in Yogyakarta. Keywords: Partograf, labor, midwives private practice